Gambaran Jamur Candida Sp Pada Handuk Anak Kos - Pagayang, Rektoviana Andi Randa; Suparno Putera Makkadafi; Nurul Anggrieni (Politeknik Baubau, 2024)
Towels are a necessity for everyone to dry their body and hair. Moist towels without sunlight cause mold and bacteria growth. Candida sp is an infection of the skin that usually develops on nails and body parts. This study aims to identify and determine the percentage of Candida sp fungi on towels of boarding children in Loa Jananan Ilir District conducted in March 2024, this type of research is descriptive with a Cross Sectional design. The number of samples in this study with 44 samples taken randomly Spada towels boarding children. From the identification obtained 47% of boarding towels contained Candida sp. It is necessary to pay more attention to personal hygiene, especially for boarding school children, so that health problems, especially those caused by the Candida Sp fungus, can be minimized.